The art of strategic leadership : - Stowell, Steven J. (Wiley, 2016)
The Art of Strategic Leadership will help you deepen and broaden your understanding of the core qualities of strategic leadership, leaving you better equipped to lead yourself and your team to a better place and create greater value for customers, owners, and employees.